Promoting Young Learners’ English Vocabulary Acquisition Using Picture Word Inductive Model Focusing On Indonesian Culture: English - Dhea Ayu Masruroh; Slamet Asari; Ulfatul Ma'rifah (Prodi Tadris Bahasa Inggris, 2024)
This study aims to analyze the utilization of the Picture word inductive model focusing on Indonesian culture to improve the English vocabulary acquisition ability of grade 5 students at Ban Erawan school, Thailand. The method used in this study was a quasi-experimental design type involving two groups, namely the experimental group and the control group. The researcher collected quantitative data by distributing pre-test and post-test to 30 students in the experimental and control groups. The researcher analyzed the data obtained from the post-test scores of the experimental group and the control group using the Mann-Whitney test on the SPSS application. From the results of the quantitative analysis, it is known that there is a difference in vocabulary acquisition between the experimental group and the control group with the significant level p<0,05 (p=.000). This suggest that Picture Word Inductive model focusing on Indonesian culture was proven to improve students' English vocabulary acquisition. In addition, students gave positive responses during data collection. The selection of learning media that is interesting and favored by students can facilitate the learning process of students and increase student motivation.